5HTR3A‐driven GFP labels immature olfactory sensory neurons. Issue 7 (27th February 2017) - Finger, Thomas E.; Bartel, Dianna L.; Shultz, Nicole; Goodson, Noah B.; Greer, Charles A.
Abstract: The ionotropic serotonin receptor, 5‐HT3, is expressed by many developing neurons within the central nervous system. Since the olfactory epithelium continues to generate new olfactory sensory neurons (OSNs) throughout life, we investigated the possibility that 5‐HT3 is expressed in the adult epithelium. Using a transgenic mouse in which the promoter for the 5‐HT3a subunit drives expression of green fluorescent protein (GFP), we assessed the expression of this marker in the olfactory epithelium of adult mice. Both the native 5‐HT3a mRNA and GFP are expressed within globose basal cells of the olfactory and vomeronasal epithelium in adult mice. Whereas the 5‐HT3a mRNA disappears relatively quickly after final cell division, the GFP label persists for about 5 days, thereby labeling immature OSNs in both the main olfactory system and vomeronasal organ. The GFP‐labeled cells include both proliferative globose basal cells as well as immature OSNs exhibiting the hallmarks of ongoing differentiation including GAP43, PGP9.5, but the absence of olfactory marker protein. Some of the GFP‐labeled OSNs show characteristics of more mature yet still developing OSNs including the presence of cilia extending from the apical knob and expression of NaV1.5, a component of the transduction cascade. These findings suggest that 5‐HT3a is indicative of a proliferative or developmental state, regardless of age, and that the 5‐HT3A GFP mice may prove useful for future studies of neurogenesis in the olfactory epithelium. J. Comp. Neurol. 525:1743–1755, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Immature olfactory receptor neurons in the olfactory epithelium of a P10 mouse, like those in adults, exhibit GFP fluorescence driven by the serotonin 5‐HT3A receptor promoter whereas mature receptor neurons are colored red by staining for OMP.